Optimization and characterization of rice–pigeon pea flour blend using extrusion cooking process. Issue 1 (27th January 2021) - Banki, Ndaliman Mohammed; Salihu, Aliyu; Muhammad, Aliyu; Bala, Shuaibu Mallam
Abstract: This study was carried out to formulate rice and pigeon pea flour blend with the aim of providing nutrient‐enriched and inexpensive food for developing countries where the raw materials are found in abundance. Three factors (screw speed, feed moisture content and feed blend composition) affecting the extrusion cooking process were subjected to face‐centred central composite design (FCCCD), and physical properties were used as the response. Analysis of variance showed that the developed quadratic model was significant with coefficient of determinations ( R 2 ) of 0.96 for expansion index, 0.93 for bulk density and 0.88 for water absorption index. Validation experiments were carried out where four rice–pigeon pea flour blends were subjected to physical, mineral and amino acid analyses. Formulation 3 set at screw speed, feed moisture content and feed blend composition of 220 rpm, 30% and 25%, respectively, led to maximum expansion index of 9.98 ± 0.15, bulk density of 0.12 ± 0.01 g/mL and water absorption index of 6.41 ± 0.07. There was significant ( p < 0.05) increase in essential amino acids in all the developed rice–pigeon pea flour blends, and Formulation 3 was found to be two‐ and fivefold higher in terms of methionine and lysine contents, respectively, than the control (extruded rice). Similarly, calcium (3.41 ± 0.07 mg/100 g), iron (12.64 ± 0.03 mg/100 g) and zinc (9.33 ± 0.02 g/100 g) contents in Formulation 3 were significantly ( p < 0.05) higher than the values of 1.19 ± 0.13, 5.89 ± 0.10 and 2.67 ± 0.05 mg/100 g recorded, respectively, for the extruded rice (control). In conclusion, the extruded rice–pigeon pea flour blend showed better physical properties and nutritional quality than the extruded rice.